Dose and temporal evaluation of ethylene oxide‐induced mutagenicity in the lungs of male big blue mice following inhalation exposure to carcinogenic concentrations. (22nd March 2017) - Manjanatha, Mugimane G.; Shelton, Sharon D.; Chen, Ying; Parsons, Barbara L.; Myers, Meagan B.; McKim, Karen L.; Gollapudi, B. Bhaskar; Moore, Nigel P.; Haber, Lynne T.; Allen, Bruce; Moore, Martha M.
Abstract : Ethylene oxide (EO) is a direct acting alkylating agent; in vitro and in vivo studies indicate that it is both a mutagen and a carcinogen. However, it remains unclear whether the mode of action (MOA) for cancer for EO is a mutagenic MOA, specifically via point mutation. To investigate the MOA for EO‐induced mouse lung tumors, male Big Blue (BB) B6C3F1 mice (10/group) were exposed to EO by inhalation, 6 hr/day, 5 days/week for 4 (0, 10, 50, 100, or 200 ppm EO), 8, or 12 weeks (0, 100, or 200 ppm EO). Lung DNA samples were analyzed for cII mutant frequency (MF) at 4, 8 and 12 weeks of exposure; the mutation spectrum was analyzed for mutants from control and 200 ppm EO treatments. Although EO‐induced cII MFs were 1.5‐ to 2.7‐fold higher than the concurrent controls at 4 weeks, statistically significant increases in the cII MF were found only after 8 and 12 weeks of exposure and only at 200 ppm EO ( P ≤ 0.05), which is twice the highest concentration used in the cancer bioassay. Consistent with the positive response, DNA sequencing of cII mutants showed a significant shift in the mutational spectra between control and 200 ppm EO following 8 and 12 week exposures ( P ≤ 0.035), but not at 4 weeks. Thus, EO mutagenic activity in vivo was relatively weak and required higher than tumorigenic concentrations and longer than 4 weeks exposure durations. These data do not follow the classical patterns for a MOA mediated by point mutations. Environ. Mol. Mutagen. 58:122–134, 2017. © 2017 Wiley Periodicals, Inc.